Epidemiological and clinical characteristics of survivors of SARS-COV-2 infection : a descriptive study - Olavegogeascoechea, Pablo Alejandro (2022)
In March 2020, the World Health Organization (WHO) declared a pandemic for coronavirus 19. Typical symptoms were fever, cough, asthenia, dyspnea, and muscle pain. Pulmonary and central nervous system compromise presented challenging characteristics for healthcare physicians. The objectives of this study were to identify epidemiological and clinical characteristics of SARS-COV-2 infection survivors in a region of Argentina and to determine differences between gender, age groups, year of infection, and evolution time since diagnosis.